Tocilizumab for the Treatment of Mevalonate Kinase Deficiency - Nadia K. Rafiq; Helen Lachmann; Frodi Joensen; Troels Herlin; Paul A. Brogan (Case Reports in Pediatrics, 2018)
Mevalonate kinase deficiency (MKD) is a severe autoinflammatory disease caused by recessive mutations in MVK resulting in reduced function of the enzyme mevalonate kinase, involved in the cholesterol/isoprenoid pathway. MKD presents with periodic episodes of severe systemic inflammation, poor quality of life, and life-threatening sequelae if inadequately treated. We report the case of a 12-year-old girl with MKD and severe autoinflammation that was resistant to IL-1 and TNF-α blockade. In view of this, she commenced intravenous tocilizumab (8 mg/kg every 2 weeks), a humanised monoclonal antibody targeting the IL-6 receptor (IL-6R) that binds to membrane and soluble IL-6R, inhibiting IL-6-mediated signaling. She reported immediate cessation of fever and marked improvement in her energy levels following the first infusion; after the fifth dose, she was in complete clinical and serological remission, now sustained for 24 months. This is one of the first reported cases of a child with MKD treated successfully with tocilizumab and adds to the very limited experience of this treatment for MKD. IL-6 blockade could therefore be an important addition to the armamentarium for the treatment of this rare monogenic autoinflammatory disease.